FBG force-testing ring for bridge cable force monitoring and temperature compensation - Li, X.; Ren, W.; Bi, Kaiming (Elsiver, 2015)
Intelligent monitoring of cable force is of vital importance in the safe operation of cable-supported bridges. For the long-term cable force monitoring, this paper is aimed at proposing a new type of fiber Bragg grating (FBG) force-testing ring. The mounting FBG sensors to the ring is designed by using the bolts to fix the sensors so that the replacement of FBG sensor elements can be achieved once the FBG sensors are failed during the long-term service. The convex platforms on both top and bottom surfaces of elastomer are designed to minimize the number of FBG sensor. The theoretical and experimental investigations are carried out to verify the feasibility and effectiveness of proposed FBG force-testing ring for the cable force monitoring and temperature compensation. The theoretical results have shown that the temperature effect is almost the same whenever the FBG force-testing ring is restrained between the anchor plate and the nut during the real application or in a free state. The formula to compensate the temperature effect is proposed accordingly. This new FBG force-testing ring is then used in a real arch bridge structure to monitor the cable forces. It is demonstrated that the new type of FBG force-testing ring has a higher accuracy of cable force measurements and temperature effect can be effectively compensated.